Efektivitas Pelaksanaan Itsbat Nikah terhadap Kepastian Hukum Status Perkawinan dan Hak Anak di Kecamatan Wuluhan Kabupaten Jember - Supianto Supianto; Tioma Roniuli Hariandja (Fakultas Hukum Universitas Islam Jember, 2016)
Based to The relegoius official files of Wuluhan district about public interest to follows program of “Itsbat Nikah” in district Wuluhan since 2015 until 2016 there was an increase. At first people timidly followed the socialization of “Itsbat Nikah” by The relegoius official of Wuluhan district, but over time the people interest to followed, especially from poor society. Case endorsement (Itsbat) Nikah is the marriage which was held by a religion but not recorded in Pegawai Pencatat Nikah(PPN) submitted by the couple of marriage or by her husband or by his wife or by their children or by some person interst which document of marriage them. They must submit to court of religion on the district were them stay. The effectiveness of the law is the process of the law became effective. The situation can be reviewed on the basis of some measure of effectiveness, namely: Rules or Regulations applicable (Law); Law Enforcement (Personnel of Government); Facilities and amenities; Society and Culture. Results of analysis that’s the rule of law is already complete from the mandate UUD 1945, UU No. 1/1974 About Marriage and all Regulation of Legislation that supports, must do “Itsbat Nikah” to thepeople who don’t recomended by Pegawai Pencatat Nikah (PPN).